La trasparenza: immaginario politico e dimensione globale - Daniel Pommier Vincelli (Im@go. A Journal of the Social Imaginary, 2020)
Trasparency has become a beacon of global politics. No normative and political concept has reached a widespread popularity than institutional transparency. Most of world nations have enacted statutes and policies favoring access to public records and accountability of the administrative, economic and political centers of authority. Transparency « belongs » to contemporaineity peering with other technological- political innovations as open government and e-democracy. Neverthless the idea of a transparent state is other than recent, laying its foundation in early XX century. Transparecny is the product of a given historical imaginary based on powerful metaphors like the «glass house » (Italy) or the «sunshine as best disinfectant » (United States). Relying on the political theory of social imaginaries (Yacob Ezrahi) this paper aims to de-construct the dynamics of institutional transparency. The idea of a transparent state offers the illusion of a self-evident political realm whose secrets could be « seen » or « taken » by an informed citizenry. The imaginary of transparency collides with the contradictions and limits of actual transparency, by forming a hiathus between reality and expectations.